INOVASI MESIN HAMMER MILL JAGUNG HORIZONTAL SEBAGAI TEKNOLOGI PRODUKSI PAKAN TERNAK ORGANIK - Teguh Wiyono; Desi Tri Utami; Luluk Takari Sarjana Rini (Journal of Automotive Technology Vocational Education, 2025)
This study aims to evaluate the innovation of a horizontal corn hammer mill machine as a technology to support the improvement of efficiency and quality in livestock feed production. The study used an applied experimental design with a quantitative approach to assess the technical performance of the machine. The treatment variables included variations in rotor speed and hammer design, while the response variables included production capacity, electricity consumption, and particle size distribution of the milled product. The study was conducted on a small to medium production scale using dry shelled corn as feed raw material. Data collection was carried out through controlled machine performance testing, then analysed descriptively and quantitatively by comparing the average values of each performance parameter. The results showed that the horizontal corn hammer mill machine with a driving power of 5.5 HP and a rotation speed of 2500 rpm was capable of achieving a production capacity of up to 300 kg/hour with a relatively compact machine design. The machine demonstrated competitive efficiency compared to similar machines and was able to produce more uniform corn particle sizes, which contributed to improved physical feed quality. The integration of machine design, material flow control, and appropriate operational parameters made this technology applicable and potentially widely applicable in small to medium-scale livestock feed businesses. Keyword: hammer mill, animal feed production, particle size, corn grinding